EKSPERIMENTASI MODEL PEMBELAJARAN GROUP INVESTIGATION BERBANTUAN CD INTERAKTIF TERHADAP HASIL BELAJAR MATA KULIAH ANALISIS REAL DITINJAU DARI KEMAMPUAN AWAL MAHASISWA - Eka Putra Wahyu Suminar; Aziz Ahmadi (Jurnal Humaniora, 2017)
This study is a quasi experimental research with factorial design 2×3.This study aims to test the effectiveness of the use of group investigation model with interactive CD in the course of analisis real toward students initial ability. This research was conducted at STKIP PGRI Pacitan in 2016. Data analysis techniques is two way ANOVA. The research finding is the student learning achievement using group investigation with interactive CD is better than the student learning achievement using group investigation with paper task. Furthermore, the student learning achievement from the high group of initial ability and the middle group of initial ability are better than the student learning achievement of the lower group of initial ability. But between the high group of initial ability and the middle group of initial ability, the student learning achievement is not significantly different.